X^2 + 7X + 18 = 0
try the discriminant
b^2 - 4ac
7^2 - 4(1)(18)
49 - 72 < 0
so, no real roots
and no factors of 18 add to 7
9x+6 = 7x+18 9x-7x = 18-6 2x = 12 x = 6
7x + 6 = -18 7x = -24 x = -24/7 x = -3.428571 recurring (that is, -3.428571428571...)
(x2 + 7x - 18) = (x + 9)(x - 2)
(x + 3)(x + 4)
It is an equation and the value of x is 2
This is only true if x = -31.
-((x + 2)(x - 9))
x2+7x+12=0usually this means to factor the equation.factored this equation would be...(x+3)(x+4)
7x = 18 - 2x 7x + 2x = 18 9x = 18 x = 2
4x+6-7x+9=18-3x+15=18-3x=3x=-1
(3b + 7x)(3b + 7x) or (3b + 7x)2
Do you mean: 5x + 9 - 7x + 6 = x - 18 If so, you can solve this question at this manner: -2x + 15 = x - 18 3x = -3 x = -1